Breaking the code applying genetic techniques to human disease - Rees, Rod ([S.l.] : Video Education Australiasia [production company] ; [S.l.] : Human Relations Media [distributor], 1996)
This two-part program outlines the principles of genetic engineering and looks in detail at their application to study and treatment of several major inheritaed diseases affecting humans
Executive producer, David Brown ; editor, David Brown
Narrator: Justin Shortal
Keywords: Genetic engineering; Genes